THE EFFECTIVENESS OF BINAHONG LEAF EXTRACT (Anredera cordifolia (Ten.) Steenis) AND MEFENAMIC ACID AS ANTI INFLAMATION TO WHITE MALE RAT INDUCED BY KARAGENIN - Betta Kurniawan; Novita Carolia; Abigail Pheilia (Fakultas Kedokteran Universitas Lampung, 2014)
Background: Binahong (Anredera cordifolia (Ten.) Steenis) has been used by people as a herb medicine to threat wound, diabetes, ans choleterol. The examination of effectiveness binahong leaf exctract on rat food edema of Sprague Dawley strain induced with 1% of karagenin. Method: The study method was modification of Winter (1962). This study was an experimental design with pre and post test control group design. The Rats were divided into five treatment groups (negative control with distilled water provision, positive control with the administration of mefenamic acid, and three groups treated with the extract dose binahong 25.2 mg/200 g BW, 50.4 mg/200 g BW, and 100.8 mg/200 g BW). Result: This study showed binahong leaf extract has anti-inflammatory power on the positive control group, the extract dose binahong were 25.2 mg/200 g BW, 50.4 mg/200 g BW, and 100.8 mg/200 g BW respectively for 11.00 %, 5.17%, 10.12%, and 1.92%. Conclusion: The highest dose of binahong extract as anti-inflammatory effects in this study were 50.4 mg/200 g BW. [JuKe Unila 2014; 4(8):151-157]